The Medical Technology Internship experience - Montiadora, Jay DG
Background of the Study: Intership in Medical Laboratory Science program is a hands-on demonstration of interns? required competencies in an actual clinical laboratory setting. Objectives: This study described actual learning experiences of medlab students in clinical laboratory during their internship. It determined highlights in interns? experiences that contributed to their development of professionalism and confidence to begin practice. Lastly, it determined factors that influenced their learning. Methodology: The study was a qualitative research design. It utilized key informant interviews, site observations and secondary data analysis. The study settings included public and private tertiary clinical laboratories accredited for internship program. Purposive sampling was made in choosing ten male and female interns as key informants from each of public and private laboratory. As for laboratory staff, they were eight male and female employed with responsibilities in teaching interns. A guide questionnaire for both group of informants was used to gather perceptions. Site observations utilized anecdotal records & time and motion tool that observed interns. Data were analyzed according to consistent and recurring themes. Results: Both study settings utilized the old curriculum recommended by the Commission on Higher Education (CMO No. 14 s2006). They only recognized the new guidelines (CMO No. 13 s2017) but do not implement it yet. Clinical teaching strategy was preceptorship and staff acted as supervisors. Facilitating factors for clinical learning included interns? approach to learning, opportunity to perform, independence, teaching approaches and behavior of staff. Obstructing factors included unclear intern-staff relationship, laboratory?s own shortcomings, and interns? attitudes. Other factors that affected learning included prior exposure to clinical laboratory, transfer of learning through official orientation, and informal endorsement. Staff?s satisfaction in teaching interns was recorded as well. Conclusion and Recommendations: Preceptorship was the prevailing clinical teaching strategy. Staff acted as supervisor, assessor, and on-the-job role model. The old curriculum (CMO 14 s2006) was still followed. Interns gain confidence through independence, opportunities to perform and receiving feedback. However, unclear intern-staff relationship and punitive environment affects clinical learning. Staff were satisfied in teaching interns although workload affects clinical learning. Staff were satisfied in teaching interns although workload affects this satisfaction. Longitudinal methodoloy and longer site observation should be considered for future study.